II-06 Therapeutic blockade of immune complex-mediated glomerulonephritis by highly selective inhibition of bruton's tyrosine kinase. (31st August 2016) - Chalmers, Sammy; Doerner, Jessica; Bosanac, Todd; Khalil, Sara; Smith, Dustin; Harcken, Christian; Dimock, Janice; Der, Evan; Herlitz, Leal; Webb, Deborah; Seccareccia, Elise; Feng, Di; et al.
Abstract : Background: Lupus nephritis (LN) is a potentially dangerous end organ pathology that affects upwards of 50% of patients with systemic lupus erythematosus (SLE). Classical treatments for this condition have targeted the adaptive immune response and/or autoantibodies, rather than the inflammatory process itself. Besides its role in B cell development, Bruton's tyrosine kinase (BTK) is important for Fc receptor signalling and macrophage polarisation. Furthermore, increasing evidence points to the role of the innate immune system, and particularly macrophages, in the pathogenesis of lupus nephritis. Materials and methods: In this study, we investigated the effects of a novel, highly selective and potent BTK inhibitor, BI-BTK-1, in an inducible model of LN in which female 129/SvJ mice receive nephrotoxic serum (NTS) containing anti-glomerular antibodies. Mice were treated once daily with vehicle alone or BI-BTK-1 (0.3–10 mg/kg, n = 16/group), either prophylactically or therapeutically. Results: When compared with control treated mice, NTS-challenged mice treated prophylactically with BI-BTK-1 exhibited significantly attenuated disease which was dose dependent, as measured by proteinuria, serum creatinine, and serum BUN. Histological assessment confirmed marked renal protection in the BI-BTK-1 treatment groups. BI-BTK-1 treatment resulted in decreased recruitment of inflammatory monocytes from the splenic reservoir, and a decrease in infiltrating IBA-1+ cells as well as C3 deposition within the kidney. RT-PCR on whole kidney RNA and serum profiling indicated that BTK inhibition significantly decreased levels of LN-relevant inflammatory cytokines and chemokines. Renal RNA expression profiling by RNA-seq revealed that BI-BTK-1 dramatically modulated pathways related to inflammation and glomerular injury. Importantly, when administered therapeutically, BI-BTK-1 reversed established proteinuria and improved renal histopathology. Moreover, preliminary results confirm the efficacy of BI-BTK-1 in the spontaneous MRL-lpr/lpr murine lupus model as well. Conclusion: Our results highlight the important role for BTK in the pathogenesis of immune complex-mediated nephritis. These results, together with additional studies by our group showing comparable efficacy with other small molecule macrophage inhibitors in nephrotoxic serum nephritis and spontaneous lupus, point to macrophage modulation as a promising therapeutic target for LN and possibly other immune related glomerulopathies.